Comparative study on efficacy of fistulotomy and Ligation of intersphincteric fistula tract (LIFT) procedure in management of fistula-in-ano - G., Vinay; K. S., Balasubrahmanya (International Surgery Journal, 2017)
Background: Fistula-in-ano is one of the most common benign anal conditions in daily surgical practice. Present study aims at comparing the efficacy of open fistulotomy and ligation of intersphincteric fistula tract (LIFT) procedure based on its post-operative outcomes. Methods: A comparative study was carried out among 50 subjects attending Department of Surgery, K. R. Hospital, Mysuru over a period of 10 months. Subjects of either sex diagnosed with anal fistula were included in the study. Patients with recurrent fistulas, Crohn’s disease, anal or distal rectal cancers were excluded from the study. Descriptive statistics, unpaired t-test, Fischer exact chi-square test were used to analyse the results. Results: The mean age group of the study subjects was 44.6±8.34 and 41.3±9.71 years among fistulotomy and LIFT procedure group respectively. The gender distribution showed a higher number of males (38) as compared to females (12). There was 23 inter-sphincteric, 2 trans-sphincteric fistula in fistulotomy group and 22 inter-sphincteric, 3 trans-sphincteric fistula in LIFT group. The average operative time for fistulotomy was significantly shorter at 19.6 minutes, compared with 28.4 minutes for LIFT procedure. Wound infection detected in 1 (4%) and 2 (8%) subjects in fistulotomy and LIFT groups, respectively. 1 (4%) subject among fistulotomy group developed anal incontinence. The average healing time for fistulotomy was 8 weeks compared to 3 weeks for LIFT procedure. Total 3 (12%) subjects developed recurrence in LIFT procedure, but no recurrence was observed in fistulotomy group. Conclusions: LIFT procedure is effective and sphincter saving technique for fistula in ano with shorter healing time and lower incidence of postoperative anal incontinence, as compared to open fistulotomy.